Screening tool to identify adolescents living with HIV in a community setting in Zimbabwe: A validation study - Bandason, Tsitsi; Dauya, Ethel; Dakshina, Subathira; McHugh, Grace; Chonzi, Prosper; Munyati, Shungu; Weiss, Helen A.; Simms, Victoria; Kranzer, Katharina; Ferrand, Rashida Abbas (PloS one, 2018)
A simple cost-effective strategy to pre-screen for targeted HIV testing can have substantial benefit in high burden and resource limited settings. A 4-item (previous hospitalisation, orphanhood, poor health status, and recurring skin problems) screening tool to identify adolescents living with HIV has previously shown high sensitivity in healthcare facility settings. We validated this screening tool in a community setting, in Harare, Zimbabwe in a community-based HIV prevalence survey. A community-based HIV prevalence survey was conducted among individuals aged 8-17 years with guardian consent and child assent and residing in 7 communities during the period February 2015 to December 2015. Participants without previously diagnosed HIV were evaluated for the probability of having HIV using the screening tool. HIV status was defined using an anonymous HIV test which was done using Oral Mucosal Transudate (OMT). A questionnaire was also administered to ascertain self-reported HIV status and screening tool items. The validity of a 4-item screening tool was tested. Sensitivity and specificity of the screening tool was assessed against the HIV status based on OMT result. Prevalence survey participants were 5386 children who had an HIV test result, aged 8-17 years. However, 5384, who did not report testing HIV positive and responded to all screening tool item questions were included in the validation. Their median age was 12 (IQR: 10-15) years, 2515 (46.7%) were male. HIV prevalence was 1.3% (95% CI:1.0-1.8%). The 4-item screening tool had poor accuracy with an area under the receiver operating curve of 0.65(95% CI: 0.60-0.72) at a cut-off score≥1. Its sensitivity was 56.3% (95% CI:44.0-68.1%) and specificity of 75.1% (95% CI:73.9-76.3%), PPV of 2.9% (95% CI:2.1-3.9%) and a NPV of 99.2% (95% CI:98.9-99.5%). The number needed to test to diagnose one child using the screening tool was 55% lower than universal testing for HIV. Use of the 4-item screening tool could be a strategy that can be adopted to identify children living with HIV in a community setting in resource limited settings by reducing the number needed to test compared to universal testing since it is inexpensive, easy to administer and not harmful. However, screening items adapted to a community setting need to be explored to improve the performance of the screening tool.